1997
DOI: 10.2307/3345425
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Faculty, Peer, and Self-Evaluations of Applied Performances

Abstract: This study is the second in a series examining relationships among faculty, peer, and self-evaluations of applied music end-of-semester performances. At three locations, college and university voice, percussion, woodwind, brass, and stringed instrument instructors rated undergraduate performances. Later, the performers rated the same set of performances (one of which was their own) on videotape. Ranging from .23 to .93, total score faculty interjudge reliability was mixed. Total score interjudge reliability am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
78
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 15 publications
13
78
1
Order By: Relevance
“…The stability of assessment validity is also influenced by differences in the individuals being assessed. Related studies have found that self-assessment results usually exceed the results of teacher assessment and the consistency of self-peer assessment is usually higher than that of self-teacher assessment (Bergee, 1997;Ross et al, 1999). Boud and Falchikov (1989) found that when self-assessment affects ranking within overall classroom scores, students tend to overestimate their abilities.…”
Section: Self-assessmentmentioning
confidence: 97%
“…The stability of assessment validity is also influenced by differences in the individuals being assessed. Related studies have found that self-assessment results usually exceed the results of teacher assessment and the consistency of self-peer assessment is usually higher than that of self-teacher assessment (Bergee, 1997;Ross et al, 1999). Boud and Falchikov (1989) found that when self-assessment affects ranking within overall classroom scores, students tend to overestimate their abilities.…”
Section: Self-assessmentmentioning
confidence: 97%
“…Each dimension on Form B was rated lower than its counterpart on Form A (since the number &dquo;1&dquo; is considered the &dquo;best&dquo; score, lower scores or ratings are indicated by higher numbers). Paired-samples t-tests revealed significant differences between forms at the .05 level or lower in the following dimensions: tone ( t = -2.27, p = .027), diction ( t = -2.40, p=.02), blend ( t = -3.36, p = .001 ) , intonation ( t = -2.34, p = .023), rhythm ( t = -2.80, p = .007), balance ( = -4.09, p < .001 ) , total score ( = -3.94, p < .001), and rating ( (Garman, Barry, & DeCarbo, 1991;Bergee, 1988Bergee, , 1989Bergee, , 1993Bergee, , 1997Bergee, , 2003 The additional analysis of the means of dimensions, total score, and overall ratings corroborates the above comments (see Table 1 and above t-test results). Form B yielded significantly different ratings in every dimension except interpretation, suggesting that the adjudicators in this setting rated the choirs more severely when using Form B.…”
mentioning
confidence: 99%
“…To this point, researchers have approached competitions from the production perspective, focusing in particular on factors that affect the objectivity of the jury. Elaborating on the figures reported in scale development and validation studies on evaluations of musical performance by Abeles (1973), Bergee (1997), Cooksey (1977), Fiske (1975), and Zdzinski and Barnes (2002), which demonstrated that judges could reliably evaluate performances in their specialization, Smith (2004) examines the ability of jury panels to not only evaluate performances but also rank performances as required by music competition. Using a panel of five judges and a 9-point scale, Smith demonstrated that a five-judge panel showed high inter-judge reliability, and as few as three judges are sufficient to reliably rank order musical performance.…”
Section: The Perceived Tension Between Production and Performancementioning
confidence: 99%